East African agriculture and climate change: A comprehensive analysis - Madagascar - Vololona, Mireille Rahaingo; Kyotalimye, Miriam; Thomas, Timothy S.; Waithaka, Michael (International Food Policy Research Institute, 2012)
This summary note is an excerpt from the chapter on Madagascar that will appear in the peer-reviewed IFPRI monograph, East African Agriculture and Climate Change: A Comprehensive Analysis.